Importance Of Newspaper Reading Habit For Social Science Students: An Analytical Study (Journal of Namibian Studies : History Politics Culture, 2022)
The study aimed to find out how far newspaper reading habit was important for Social Science students. In doing so the paper took into consideration the perception of students towards newspaper reading. To achieve the objective a sample of 105 social science college students were chosen. Findings revealed that newspaper reading habit among students was moderate and majority of students were interested in entertainment news, education / career news and political news. Also, it was found that newspaper as a source of information has high importance for Social Science students.